1990
DOI: 10.1080/07315724.1990.10720343
|View full text |Cite
|
Sign up to set email alerts
|

Action of ornithine alpha-ketoglutarate, ornithine hydrochloride, and calcium alpha-ketoglutarate on plasma amino acid and hormonal patterns in healthy subjects.

Abstract: Ornithine alpha-ketoglutarate (OKG) has been useful as an adjuvant of enteral and parenteral nutrition. However, its metabolism and mechanism of action remain unclear although it is known that alpha-ketoglutarate (alpha KG) and ornithine (ORN) follow, in part, common metabolic pathways. Six fasting healthy male subjects underwent three separate oral load tests: (i) they received 10 g of OKG (i.e., 3.6 g of alpha KG and 6.4 g of ORN); (ii) 6.4 g of ORN as ornithine hydrochloride, and (iii) 3.6 g of alpha KG as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 21 publications
2
54
0
Order By: Relevance
“…One of the reasons for this large difference is considered to be the different ornithine amounts ingested. Subjects ingested over 170 mg per kilogram of body mass in Bucci et al [10] and Cynober et al [9]'s study, who reported positive effect, but subjects ingested no more than 100mg per kilogram of body mass in the other studies. Moreover, subjects in all studies were mainly body builders or weight lifters who routinely conducted high intensity strength training.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of the reasons for this large difference is considered to be the different ornithine amounts ingested. Subjects ingested over 170 mg per kilogram of body mass in Bucci et al [10] and Cynober et al [9]'s study, who reported positive effect, but subjects ingested no more than 100mg per kilogram of body mass in the other studies. Moreover, subjects in all studies were mainly body builders or weight lifters who routinely conducted high intensity strength training.…”
Section: Introductionmentioning
confidence: 88%
“…Until now, arginine and ornithin have been mainly used to examine the effect on growth hormone secretion by oral amino acid ingestion [5][6][7][8][9][10]. However, there were mixed reports on the effect of growth hormone secretion by ornithine ingestion (negative reports: 5-9, Positive reports: 9, 10).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, studies indicate that OKG administration improves gut morphology and function, and enhances intestinal adaptation under stress conditions (Dumas et al, 1998;Cynober, 1999). The positive action of the OKG on the gut would seem be due to the synergic effect exerted by its constituents (Cynober et al, 1990). This suggests that the simultaneous administration of Orn and AKG is necessary to obtain the same effects found with OKG.…”
Section: Alpha-ketoglutaric Acid In Growing Ratsmentioning
confidence: 89%
“…It was found that AKG, as well as digestive enzymes, interacts with enterocytes and is involved in amino acid biosynthesis, offering advantages in a catabolic state and thus may also affect the rate of gluconeogenesis in mucosa cells [2,21,34,[36][37][38]. On the other hand, AKG in enterocytes undergoes amination and appears in the plasma as glutamate [36] which may stimulate insulin exocytosis from β-cells in response to glucose stimulation [39].…”
Section: Discussionmentioning
confidence: 99%